The impact of the affordable care act and Medicaid expansion on colorectal cancer screening: Evidence from the 5th year of Medicaid expansion - Michael A. Preston; Mahmoud Manouchehri Amoli; Askar S. Chukmaitov; Alex H. Krist; Bassam Dahman (Cancer Medicine, 2024)
Abstract Background Colorectal cancer screening rates remain suboptimal, particularly among low‐income populations. Our objective was to evaluate the long‐term effects of Medicaid expansion on colorectal cancer screening. Design, Setting, and Participants This cross‐sectional study analyzed data from 354,384 individuals aged 50–64 with an income below 400% of the federal poverty level (FPL), who participated in the Behavioral Risk Factors Surveillance System from 2010 to 2018. A difference‐in‐difference analysis was employed to estimate the effect of Medicaid expansion on colorectal cancer screening. Subgroup analyses were conducted for individuals with income up to 138% of the FPL and those with income between 139% and 400% of the FPL. The effect of Medicaid expansion on colorectal cancer screening was examined during the early, mid, and late expansion periods. Main Outcomes and Measures The primary outcome was the likelihood of receiving colorectal cancer screening for low‐income adults aged 50–64. Results Medicaid expansion was associated with a significant 1.7 percentage point increase in colorectal cancer screening rates among adults aged 50–64 with income below 400% of the FPL (p < 0.05). A significant 2.9 percentage point increase in colorectal cancer screening was observed for those with income up to 138% the FPL (p < 0.05), while a 1.5 percentage point increase occurred for individuals with income between 139% and 400% of the FPL. The impact of Medicaid expansion on colorectal cancer screening varied based on income levels and displayed a time lag for newly eligible beneficiaries. Conclusions Medicaid expansion was found to be associated with increased colorectal cancer screening rates among low‐income individuals aged 50–64. The observed variations in impact based on income levels and the time lag for newly eligible beneficiaries receiving colorectal cancer screening highlight the need for further research and precision public health strategies to maximize the benefits of Medicaid expansion on colorectal cancer screening rates.